2017
DOI: 10.3126/bjhs.v1i1.17100
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Post Operative Wound Infection Following the Use of Antibiotics in Clean Contaminated Head and Neck Surgery in a Tertiary Care Centre in Eastern Nepal

Abstract: Introduction Post operative wound infection continues to be the major concern even after the appropriate antibiotic coverage.Objective To find out the incidence of post operative wound infection following the use of antibiotics in clean contaminated head and neck surgery in a tertiary care centre in Eastern Nepal.Methodology It is a prospective study conducted at Department of Otorhinolaryngology and Head and Neck Surgery, Nobel Medical  College Teaching Hospital, Biratnagar from 14th April 2013 to 12th April … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Inadequate sterilization of devices is one of several factors that contribute to HAIs, which are more common in low- and middle-income countries (pooled prevalence of affected patients = 10.2%; 95% CI 9.0% - 13.0%) than in high-income countries (pooled prevalence of affected patients = 7.1 per 100 patients; 95% CI 6.5–7.8), with surgical site infection (SSI) being the most frequent type of HAI [5,11]. Tertiary care hospitals in Nepal have reported high rates of SSI (2.7 to 23.0 per 100 patients) but have not investigated a link between these infections and sterilization procedures [12–15].…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate sterilization of devices is one of several factors that contribute to HAIs, which are more common in low- and middle-income countries (pooled prevalence of affected patients = 10.2%; 95% CI 9.0% - 13.0%) than in high-income countries (pooled prevalence of affected patients = 7.1 per 100 patients; 95% CI 6.5–7.8), with surgical site infection (SSI) being the most frequent type of HAI [5,11]. Tertiary care hospitals in Nepal have reported high rates of SSI (2.7 to 23.0 per 100 patients) but have not investigated a link between these infections and sterilization procedures [12–15].…”
Section: Introductionmentioning
confidence: 99%
“…20 In contrary to the recommendations, many centers in Nepal and India, antibiotics are being prescribed for various duration following thyroidectomy. [4][5][6] In an international survey among endocrine surgeons, the patterns of antibiotic use varied widely among European, American and Asian surgeons. Most of the Asian surgeons (58.3%) almost always prescribed antibiotic prophylaxis in contrary to European surgeons whereby only 8.8% do so routinely.…”
Section: Discussionmentioning
confidence: 99%
“…4 In most of the centers in Nepal, perioperative antibiotics are still administered for varying duration. 5,6 At Patan Hospital, Nepal, study regarding use of antibiotic prophylaxis has not been done in thyroid surgery, but, a study on low risk laparoscopic cholecystectomy, regarded as clean surgery, routine use of antibiotic prophylaxis did not show added advantage in preventing SSI. 7 There is a dearth of literature regarding antibiotic prophylaxis in our set up.…”
Section: Introductionmentioning
confidence: 99%
“…HAIs can prolong a patient’s stay in the hospital, cause long-term disability, increase the financial burden for health systems, increase costs for patients and their families, and result in deaths [ 2 ]. Studies in Nepal have also shown a higher proportion of SSIs (2.7 to 23.0 per 100 patients) in patients who had undergone different surgeries in different tertiary-care hospitals [ 3 – 6 ]. The studies have indicated that inadequate reprocessing and sterilization of reusable medical devices could be one of the factors contributing to the higher rates of SSIs.…”
Section: Introductionmentioning
confidence: 99%